Enhancing the performance of a 125 cc single-cylinder, aircooled, gasoline two-stroke engine - Abdul Aziz, A.; Abdul Latiff, Z.; Mohd. Ali, M. Fawzi; Mohammad Said, M. Farid; Said, M. (2006)
A unique stepped-piston engine was developed by a group of researchers at UTM. The development work engulfs design, prototyping and testing over a predetermined period of time. The aim is to demonstrate environmental-friendly capability producing comparable output with low-fuel consumption. In its carbureted version, it incorporates a three-port transfer system and a dedicated crankcase breather. These features will enable the prototype to have high induction efficiency and to behave very much a two-stroke engine but equipped with a four-stroke crankcase lubrication system. In the final stage of development it was subjected to a series of laboratory trials. It was also tested on a small watercraft platform with promising indication of its flexibility of use as a prime mover in mobile platform. In an effort to further enhance its technology features, the researchers have embarked on the development of an addon auxiliary system. The system comprises of an engine control unit (ECU), a direct-injector unit, a dedicated lubricant dispenser unit and an embedded common rail fuel unit. This support system was incorporated onto the engine to demonstrate the finer points of environmental-friendly and fuel economy features. The outcome of this complete package is described in the paper, covering the methodology and the final characteristics of the mobile power plant.